2001
DOI: 10.1002/1522-2683(200107)22:12<2424::aid-elps2424>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion coefficient of DNA molecules during free solution electrophoresis

Abstract: The free-draining properties of DNA normally make it impossible to separate nucleic acids by free-flow electrophoresis. However, little is known, either theoretically or experimentally, about the diffusion coefficient of DNA molecules during free-flow electrophoresis. In fact, many authors simply assume that the Nernst-Einstein relation between the mobility and the diffusion coefficient still holds under such conditions. In this paper, we present an experimental study of the diffusion coefficient of both ssDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
163
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(184 citation statements)
references
References 31 publications
17
163
4
Order By: Relevance
“…The dynamics of dsDNA in solution has been a subject of a number of experimental investigations carried out by various techniques, including DLS [5], single-molecule fluorescence microscopy [6], electrophoresis [7], and TEB [8]. Fluorescence correlation spectroscopy (FCS) [9], a single-molecule technique that can provide more detailed information on the macromolecular dynamics than the classical ensemble-based methods, has been recently applied to investigation of DNA in solution [10 -12], which has lead to a controversy whether dsDNA dynamics in dilute solution is controlled by hydrodynamic interactions [10,12] or not [11].…”
supporting
confidence: 44%
See 2 more Smart Citations
“…The dynamics of dsDNA in solution has been a subject of a number of experimental investigations carried out by various techniques, including DLS [5], single-molecule fluorescence microscopy [6], electrophoresis [7], and TEB [8]. Fluorescence correlation spectroscopy (FCS) [9], a single-molecule technique that can provide more detailed information on the macromolecular dynamics than the classical ensemble-based methods, has been recently applied to investigation of DNA in solution [10 -12], which has lead to a controversy whether dsDNA dynamics in dilute solution is controlled by hydrodynamic interactions [10,12] or not [11].…”
supporting
confidence: 44%
“…Within the range of lengths studied, D L ÿ2=3 and r L 2 , and thus the results do not follow the predictions of either the Rouse or Zimm model [1]. At the same time, our data are in a very good agreement with experimental results obtained by other techniques not related to FCS [5][6][7][8] and closely follow the predictions of the semiflexible polymer theory [4]. Therefore, our results clearly demonstrate that in the range of the lengths studied, dsDNA behaves as a semiflexible polymer with strong hydrodynamic interactions [29].…”
Section: -2mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a detailed physical understanding of surface transport of DNA is currently not available. 3 For example, it is commonly known that the diffusion coefficient of DNA decreases with increase in DNA size in free solution 4 and under two-dimensional confinement. 5 However, a recent experimental study on electrophoresis of DNA on an atomic force microscopy surface showed the faster movement of longer DNA in a thin pure water film.…”
mentioning
confidence: 99%
“…The gel was stained with SYBR Gold and imaged using a UV trans-illuminator. 51 52 580 581 582 583 584 585 586 587 588 589 590 591 592 593 594 595 596 597 598 599 600 601 602 603 604 605 606 607 608 609 610 611 612 613 …”
Section: Affinity Measurementmentioning
confidence: 99%